2019
DOI: 10.1186/s40981-019-0255-9
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative anesthetic management of intestinal pseudo-obstruction as a complication of pheochromocytoma

Abstract: Background: Intestinal pseudo-obstruction, which is a rare complication of pheochromocytoma, can be caused by hypersecreted catecholamines. Case presentation: A 45-year-old woman was admitted for local recurrence of pheochromocytoma complicated by intestinal pseudo-obstruction. The intestinal pseudo-obstruction showed poor response to α-adrenergic receptor blocker and she was scheduled for surgical resection of pheochromocytoma. The surgery was uneventfully accomplished with general anesthesia combined with ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(14 reference statements)
1
1
0
Order By: Relevance
“…The latter responded well to the surgical removal of the tumor. A very similar case and outcome has been previously reported [11] .…”
Section: Discussionsupporting
confidence: 85%
“…The latter responded well to the surgical removal of the tumor. A very similar case and outcome has been previously reported [11] .…”
Section: Discussionsupporting
confidence: 85%
“…Constipation and intestinal pseudo-obstruction are occasionally observed complications of pheochromocytoma caused by hypersecretion of catecholamines, which act on alpha-2-adrenergic receptors of intestinal smooth muscle cells to decrease intestinal movement. 6 , 7 Thosani et al reported that 6% of patients with paragangliomas or pheochromocytomas experienced constipation. In addition, they reported that constipation is a complication usually observed in patients with primary tumors larger than 5 cm, as in this case, or with extensive metastatic disease.…”
Section: Discussionmentioning
confidence: 99%